Body Language - Elderfield, John; Alexander, M. Darsie; Chan, Mary; Figura, Starr; Ganz, Sarah; Gonzalez, Maria del Carmen; Museum of Modern Art (MoMA), New York (New York : Museum of Modern Art, 1999)
Orozco, José Clemente ; Weston, Edward ; Shahn, Ben ; Lange, Dorothea ; Maillol, Aristide ; Cartier-Bresson, Henri ; Cézanne, Paul ; Dijkstra, Rineke ; Johnston, Frances Benjamin ; et al.
Published on the occasion of the exhibition ModernStarts: People, Places, Things at The Museum of Modern Art, New York, October 7, 1999 - March 14, 2000
kunstcatalogus